Pengaruh Modal Usaha, Orientasi Pasar, dan Orientasi Kewirausahaan Terhadap Kinerja UKM Kota Makassar - Abbas, Djamila (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2018)
The performance of MSMEs in general varies considerably from year to year. The role of micro, small and medium enterprises (MSMEs) in the Indonesian economy is demonstrated by its population as the largest business actor, as well as its contribution in employment, the formation of gross domestic product (GDP), exports and the creation of fixed capital / investment. The problem is then divided into several sub-problems of research on whether the variable of business capital, market orientation, and entrepreneurship orientation affect the performance of SMEs Makassar City. The total population of 123 registered and not registered businesses of SMEs Makassar. Data was then analysed using multiple linear regression. The results of the research are that there is positive influence of the three variables on the performance of SMEs of Makassar City simultaneously, and also positive effect when tested partially.